Manajemen Irigasi Pembibitan Sawit (Elaeis guineensis) Presisi dengan Cropwat 8.0 - Lisma Safitri (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2019)
The accurate water use information at each stage of plant growth is important to better understand the efficient and precise crop water requirement for optimal plant productivity. Nurseries of palm oil are a phase where young palm oil requires extra maintenance, particularly in meeting the plant water needs. The palm oil in the nursery phase require the regular irrigation schedule due to the vulnerable root systems. The purpose of this study was to calculate the oil palm water requirement with Cropwat 8.0 toward the precise irrigation management and provide a scenario for irrigation scheduling in palm oil nursery. The study was conducted in palm oil main nurseries at KP2 Instiper Yogyakarta with site-specific climate data and soil properties. The method used is analyzing climate data and soil properties and simulating crop water requirements, actual water use and irrigation scheduling with Cropwat 8.0. Based on the results, the average of crop water requirement (ETP) of palm oil in main nursery is 3.4 mm / day. Based on the water deficit scenario from rainfall and crop water requirements, irrigation is scheduling in April for 1.4 mm, May for 18.3 mm, June for  3.5 mm, July for 44.1 mm and August for 42.8 mm. On a daily scale and taking into account the availability of soil moisture and the water retention of plant roots, the net irrigation scheduling is given at an average of 2.2 mm / day and gross irrigation of 6 mm / day which is given daily depending on rainfall and plant age.